Effectiveness of Jaw Exercises Applied in Addition to Cervical Stabilization Exercises in Individuals with Chronic Neck Pain: A Randomized Controlled Trial [Response to Letter] - Canli, Mehmet; Ozudogru, Anil; Alkan, Halil; Cigdem-Karacay, Basak (Dove Medical Press Ltd, 2026)
[Keywords Not Available]
Keywords: Spinal Manipulation; Disability Index; Reliability